Eicosanoids in Cancer: Prostaglandin E2 Receptor 4 in Cancer Therapeutics and Immunotherapy - Ching, Mc Millan; Reader, Jocelyn; Fulton, Amy M. (Frontiers in Pharmacology, 2020)
The cyclooxygenase-2 (COX-2) enzyme is frequently overexpressed in epithelial malignancies including those of the breast, prostate, lung, kidney, ovary and liver and is associated with poor outcomes. COX-2 catalyzes the metabolism of arachidonic acid to prostaglandins. In cancer, the COX-2 product prostaglandin E2 (PGE2) binds to four G-protein-coupled EP receptors designated EP1-EP4. EP4 is commonly upregulated in cancer and supports cell proliferation, migration, invasion and metastasis through activation of multiple pathways including ERK, cAMP/PKA, PI3K/AKT and NF-κB pathways. EP4 antagonists inhibit metastasis in preclinical models. Cancer stem cells, that underlie therapy resistance and disease relapse, are driven by the expression of EP4. Resistance to several chemotherapies is reversed in the presence of EP4 antagonists. In addition to tumor cell-autonomous roles of EP4, many EP4-positive host cells play a role in tumor behavior. Endothelial cell-EP4 supports tumor angiogenesis and lymphangiogenesis. Natural Killer cells are critical to the mechanism by which systemically administered EP4 antagonists inhibit metastasis. PGE2 acts on EP4 expressed on the NK cell to inhibit tumor target cell killing, cytokine production and chemotactic activity. Myeloid-derived suppressor cells (MDSCs), that inhibit the development of cytotoxic T cells, are induced by PGE2 acting on myeloid-expressed EP2 and EP4 receptors. Inhibition of MDSC leads to maturation of effector T cells and suppresses the induction of T regulatory cells. Taken together, there is growing evidence that EP4 antagonism, particularly in combination with either chemotherapy or immune-based therapies, should be investigated further as a promising novel approach to cancer therapy.